Financial Constraints and Girls' Secondary Education: Evidence from School Fee Elimination in The Gambia. (17th October 2016) - Blimpo, Moussa P; Gajigo, Ousman; Pugatch, Todd
Abstract: We assess the impact of large-scale fee elimination for secondary school girls in The Gambia on the quantity, composition, and achievement of students. The gradual rollout of the program across geographic regions provides identifying variation in the policy. The program increased the number of girls taking the high school exit exam by 55%. The share of older test takers increased in poorer districts, expanding access for students who began school late, repeated grades, or whose studies had been interrupted. Despite these changes in the quantity and composition of students, we find robustly positive point estimates of the program on test scores, with suggestive evidence of gains for several subgroups of both girls and boys. Absence of learning declines is notable in a setting where expanded access could strain limited resources and reduce school quality. Our findings suggest that financial constraints remain serious barriers to post-primary education, and that efforts to expand access to secondary education need not come at the expense of learning in low-income countries like The Gambia.